Towards the Standardization of Flow Chemistry Protocols for Organic Reactions. Issue 11 (13th September 2021) - Hone, Christopher A.; Kappe, C. Oliver
Abstract: Flow chemistry studies can sometimes be difficult to reproduce. In this article we provide guidance to scientists for experimental details that should be considered as part of any organic chemistry‐based continuous flow study. A focus is placed on information that should be provided within reported studies to enable experiments to be more easily and reliably reproduced. Topics covered include flow reactor components and assembly, important parameter effects and useful performance criteria. The article covers aspects of homogeneous systems, multiphase transformations, and catalytic reactions (homogeneous and heterogeneous). A more detailed discussion of photochemistry, biocatalysis and electrochemical flow systems is outside the scope of this review. Abstract : Making continuous flow studies easier, experimental details that should be provided as part of any organic chemistry‐based continuous flow study are presented and critically discussed. These range from flow reactor components and assembly, to important parameter effects and useful performance criteria. This review covers aspects of homogeneous systems, multiphase transformations and catalytic reactions.